Social networks and advice for new mothers: The importance of grandmothers' embeddedness. Issue 2 (12th October 2021) - Cornwell, Benjamin; Yan, Xuewen; Carlin, Rebecca F.; Fu, Linda; Wang, Jichuan; Moon, Rachel Y.
Abstract: Objective: We examine whom, among her social network members, a new mother ranks as her most important source of advice for infant care practices and how the ranking of a network member depends on their connectedness to a mother's other network members. Background: Previous research points to the influence of personal networks members' advice on parental practices. However, to design effective interventions that facilitate safe and healthy infant and childcare practices, it is important to understand who, in parents' social circles, they turn to most for advice. Method: We recruited 402 Black and White new mothers in Washington, DC. We analyze the importance rank they assign to their 1, 791 network members using nested, dyad‐level rank‐ordered logit models. Results: Connectivity to a mother's other network members and being the mother's mother (i.e., the baby's maternal grandmother) emerged as positive and significant predictors of being ranked as the most important sources of advice. Additionally, the effect of being a grandmother is stronger among grandmothers who are well connected to mothers' other network members. Conclusion: Network members who are well embedded in mothers' own networks are usually viewed by mothers as key sources of advice. Embeddedness is an especially significant condition for new mothers when ranking babies' maternal grandmothers as main advisors. Implications: We encourage future research on mothers' network members as potential targets for infant and childrearing‐related interventions.